Moral Learning in Forming Moderate Muslims on Islamic College in Malang - Susilawati, Samsul; Rahmaniah, Aniek; Yasin, A.Fattah; Wahidmurni (International Journal of Psychosocial Rehabilitation, 2020)
This article discusses how can thinking, planning, and learning strategies moral in the form of moderate Muslims in the State Islamic University of Maulana Malik Ibrahim Malang (UIN Maulana Malik Ibrahim Malang), University of Muhammadiyah Malang (UMM), and Universitas Islam Malang (Unisma). The significance of this study for the development of education is as a reference for higher education policy regulators in actualizing the values of religiousity and moral values in the learning process. Get a model of moral learning that promotes moderate Islam and forms a tolerant Muslim personality. Moral education carried out in the three PTKI, shows that moral education is not only delivered in the form of moral values cognitively, but is already at the stage of internalizing values by practicing direct moral values in the lives and activities of students every day. It is hoped that the internalization of moral education will build the character of moderate Muslims who are friendly and tolerant.